A didactic model to support the use of senses and sensors in environmental education problem solving. (22nd March 2023) - Silva, Maria João
Abstract: Problem solving, and specifically the goal of developing problem-solving competences, is a significant dimension of environmental education. Moreover, human senses and electronic sensors have been recognized as important tools in authentic problem-based learning. The purpose of this paper is to present a model to support teachers in creating didactic activities that use human senses and electronic sensors as epistemic mediators in participatory environmental education problem-based learning. The EcoSolvingS model is based on a set theoretical and practical perspectives, and on a cross analysis of a selection of environmental education problem-solving case studies. In a first part, this paper presents the dimensions of the theoretical foundations of the EcoSolvingS model. Subsequently, the results of the cross analysis of the environmental education problem-solving case studies are presented and related to the components of the EcoSolvingS model. Finally, the model is described, and its utility and future developments are discussed.